Improving Studets’ Interest Through Games Method In Learning Social Science Education - Nurhayati, Wahyu Indah (Universitas Pendidikan Indonesia, 2017)
This research is motivated by the low interest of students to social science education in class VII-J SMPN 3 Lembang. The purpose of this study is to describe the plan, implementation,result, difficulties, and solutions in the implementation of games method to improve students’ interest in learning. This esearch uses qualitative and quantitative data analysis. This research also uses classroom action research with Kemmis and Taggart model by using games as a learning method. The subject for this research is the students of class VII-J in SMPN 3 Lembang Bandung. The planning of this research includes preparing lesson plan, preparing games that will be used in each cycle, as well as preparing the research instruments according to the needs of the researcher. This research was conducted in four cycles and the result showed that there was an improvement of students’ interest in learning social science education from the first cycle until the fourth cycle. In the first cycle, to improve students’ interest in earning social science education, the researcher used Bottle Throwing Game and the result showed that the students got low score. In the second cycle, the reesearcher used Ular Naga Game and the result was a little bit better than the first cycle. In the third cycle, Hungry Bunny Game was used and the students got a good score in this cycle. For the last cycle, the researcher used Pokemon Go Game and the result showed that the students got a very good score in the last cycle. The evidence for students’ improvement in learning is marked by the number of students who feel happy when learning social science education, show their enthusiastic, and active in social science education class. The researcher found some difficulties in implementing this research, there are difficult to determine the appropriate game for the students, difficult in selecting material, and difficult in directing the students when playing the games. Those difficulties can be overcome by making a good lesso plan, reading a lot of teaching materials, and facilitate students to discuss with the group, and also make some rules when the students will do the games.